EphB4 promotes site-specific metastatic tumor cell dissemination by interacting with endothelial cell-expressed ephrinB2 - Héroult, Mélanie; Schaffner, Florence; Pfaff, Dennis; Prahst, Claudia; Kirmse, Robert; Kutschera, Simone; Riedel, Maria; Ludwig, Thomas; Vajkoczy, Peter; Graeser, Ralph; Augustin, Hellmut (Molecular cancer research, 2010)
The tyrosine kinase receptor EphB4 interacts with its ephrinB2 ligand to act as a bidirectional signaling system that mediates adhesion, migration, and guidance by controlling attractive and repulsive activities. Recent findings have shown that hematopoietic cells expressing EphB4 exert adhesive functions towards endothelial cells expressing ephrinB2. We therefore hypothesized that EphB4/ephrinB2 interactions may be involved in the preferential adhesion of EphB4-expressing tumor cells to ephrinB2-expressing endothelial cells. Screening of a panel of human tumor cell lines identified EphB4 expression in nearly all analyzed tumor cell lines. Human A375 melanoma cells engineered to express either full-length EphB4 or truncated EphB4 variants which lack the cytoplasmic catalytic domain (ΔC-EphB4) adhered preferentially to ephrinB2-expressing endothelial cells. Force spectroscopy by atomic force microscopy confirmed, on the single cell level, the rapid and direct adhesive interaction between EphB4 and ephrinB2. Tumor cell trafficking experiments in vivo using sensitive luciferase detection techniques revealed significantly more EphB4-expressing A375 cells but not ΔC-EphB4-expressing or mock-transduced control cells in the lungs, the liver, and the kidneys. Correspondingly, ephrinB2 expression was detected in the microvessels of these organs. The specificity of the EphB4-mediated tumor homing phenotype was validated by blocking the EphB4/ephrinB2 interaction with soluble EphB4-Fc. Taken together, these experiments identify adhesive EphB4/ephrinB2 interactions between tumor cells and endothelial cells as a mechanism for the site-specific metastatic dissemination of tumor cells. Mol Cancer Res; 8(10); 1297-309. ©2010 AACR.
Gesehen am 26.04.2023